Right to Privacy in Cyberspace - Abdulkhamidova Khadichabegim Ulugbek qizi; Allayorov Jaxongir Tashpolatovich (Genius Journals, 2023)
Life without the Internet and online communications now seems unimaginable. Almost all aspects of human life are now connected with the Internet. People buy goods and services online, communicate with friends and family through social networks, make bank transfers over the Internet, and much more. However, all this carries certain risks associated with the leakage of personal data and violation of the right to privacy. In cyberspace, personal data can be hacked, stolen or used for personal gain. To protect personal data and privacy rights, certain precautions must be taken, such as the use of strong passwords and anti-virus software, restricting access to personal information, and being careful when posting personal information online. In view of the indicated relevance, this scientific article is aimed at studying the features of ensuring the right to privacy of a person in cyberspace. The purpose of the scientific article is to identify the actual problems of ensuring the law under study. The methodology of a scientific article covers the application of methods of scientific analysis, synthesis, induction, deduction, sociological method of research, and generalization of scientific material. The results of the work in a scientific article are expressed in the form of proposals developed by the author of the article. The scope of the results is the legislation of the Republic of Uzbekistan and the practice of public relations related to the Internet. The general conclusion in this scientific article is the statement about the need to strengthen the legislative and legal framework for ensuring the human right to privacy in cyberspace
Keywords: Internet; human rights; cyberspace